Influence of process conditions on ultrasound‐assisted protein extraction from cold pressed tomato seed waste. Issue 12 (3rd November 2021) - Özyurt, Vasfiye Hazal; Tetik, Irmak; Ötleş, Semih
Abstract: Tomato seed waste is obtained in large amounts in tomato paste processing. In this study, ultrasound‐assisted protein extraction of tomato seed waste was used and extraction parameters were optimized using response surface methodology. Effects of independent variables (liquid:solid ratio, ultrasound duration, and extraction duration) were evaluated on the extraction yield, and optimal extraction conditions were determined as 52 ml/g, 2 min 18 s and 60 min, respectively. The optimum protein yield was found as 35.75%. Structural and physicochemical properties of tomato seed waste protein were also determined. These obtained results present important information for the determination quality characteristics of tomato seed oil in optimum extraction conditions. It can be concluded that ultrasound‐assisted extraction is an efficient technique for the extraction of protein from tomato seed waste, and the obtained protein has the potential applications in the food industry. Novelty impact statement: Defatted tomato seed cake obtained from tomato seed oil processing was used to obtain tomato seedprotein isolate. Ultrasound‐assisted extraction methods were optimized by response surface methodology to maximize protein yield. The physicochemical properties of tomato seed protein isolate were searched, whether it may be a new protein source.